Effect of sulphur dose on the productivity and quality of onions - de Souza, Luiz Felipe Gevenez [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP]; de Túlio, Fred Alberto [UNESP]; Nowaki, Rodrigo Hiyoshi Dalmazzo [UNESP] (My University, 2015)
Onions have a high demand for sulphur (S), which affects bulb productivity and quality. S, however, should be carefully applied to onion crops because it may acidify the soil and adversely affect the plants. This study evaluated the effects of S dose (0, 15, 30, 45, 60, and 90 kg ha-1) on the soil and the development, productivity, and quality of the 'Perfecta' onion cultivar. The experiment was conducted in Jaboticabal, Brazil, from 30 May to 10 October 2011. Maximum height (0.76 m), number of leaves per plant (7.2), dry weight of leaves (201.6 g), and productivity (79 t ha-1) of the 'Perfecta' onions were obtained with doses of 57, 41, 47, and 45 kg S ha-1, respectively. Onion productivity was 16% lower, when S was not applied. About 47% of total production of bulbs was ranked in classes 3 and 4, with higher commercial value. The highest percentage of bulbs (63%) in classes 3 and 4 was obtained with 47 kg S ha-1. Maximum pungency (1.5 μmol g-1) was obtained with 65 kg S ha-1, ca. 55% higher than when S was not applied. The levels of pyruvic acid, however, were low in all treatments, which ranked the cultivar as very mild with an extra-sweet flavour when provided with up to 90 kg S ha-1. The interaction between S dose and period of evaluation influenced the soil pH and S content. The increased S supply increased the levels of foliar N and S-SO4 2- and decreased Ca2+ and Mg2+.
Keywords: Allium cepa L.; Elemental S; Fertilisation; Mineral nutrition; Pungency; Pyruvic acid